The Development of Timor Deer Breeding in Tahura Wan Abdul Rachman Lampung - Xavier, Saturnino; Harianto, Sugeng Prayitno; Dewi, Bainah Sari (Jurnal Sylva Lestari, 2018)
The presence of National Forest Park (Tahura) Wan Abdul Rachman is an opportunity to be developed into ecotourism if it is well-managed and have support from stakeholders especially the local community. The purpose of this study is to know the potential of human resource, management capabilities, community support in Tahura Wan Abdul Rachman and to formulate priority development strategy of captive breeding timor deer into ecotourism. This research was conducted during February to April 2017. Data was collected by observation and interview. The data was analyzed descriptively using SWOT analysis. The result showed that the existence of captive timor deer in Tahura Wan Abdul Rachman can be developed into ecotourism because of the support from society and other stakeholder. Management Unit in Tahura Wan Abdul Rachman was implemented the functions of management such as planning, organizing, actuating and controlling. A main priority of strategy to maintain and develop the ecotourism potential based on deer breeding is by improving coordination and cooperation between UPTD Tahura Wan Abdul Rachman as the organizer of deer breeding unit with local Goverment of Lampung Province, private party and community. Keywords: deer breeding, ecotourism, human resource, management.